Realizacja koncepcji Euromiasta Gubin-Guben próbą zacieśnienia współpracy na rzecz rozwoju polsko-niemieckiego porganicza = Realization of the Eurocity concept Gubin-Guben as an attempt to enhance cooperation for the development of Polish-German borderland - Grablewska, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Guben, a town in Brandenburg land situated between the Neisse and Spree, was divided into two parts under the provisions of Potsdam Conference of 1945. Since that time, Guben and Gubin constitute "Doppelstadt", i.e., "double town". The cooperation of the two towns contributed to the development of a concept of "Eurocity Gubin-Guben" by City Councils of Gubin and Guben. The main goal of the concept was the development of the idea of Doppelstadt with one city centre in the region, which would referred to the traditions and architectural solutions of Guben before World War II.
Keywords: pogranicze polsko-niemieckie; stosunki polsko-niemieckie; Gubin; Guben; współpraca polsko-niemiecka; współpraca regionalna